PROFESIONALISME DALAM PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Ali Mustofa; Taufikurrahman; Muhammad Al Mighwar; Ujang Nurjaman (Fakultas Agama Islam Universitas Wiralodra, 2022)
The purpose of this study is to describe and analyze the what, why, and how of professionalism in education based on religion, philosophy, psychology, and sociology. The results of this study are that professionalism in education is a skill in learning which: (1) based on religion means having the idea of God's mandate that commands expertise, by behaving in a trustworthy, fair, teaching and careful manner; (2) based on philosophy means having the idea of universal science and the meaning of life as pure and original ideas, using theocentric, totality, spiritual, soulcentric, inner knowledge, and value goals ways of thinking; (3) based on psychology means having the idea of science of the mind and human behavior that wants to be humanistic, by client centered therapy, life history, and the need hierarchy model; and (4) based on sociology means having the idea of social science of prosperous development, by economic investment